Financing the capital development of the economy: A Keynes-Schumpeter-Minsky synthesis - Mariana Mazzucato; L. Randall Wray (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This paper discusses the role that finance plays in promoting the capital development of the economy, with particular emphasis on the current situation of the United States and the United Kingdom. We define both "finance" and "capital development" very broadly. We begin with the observation that the financial system evolved over the postwar period, from one in which closely regulated and chartered commercial banks were dominant to one in which financial markets dominate the system. Over this period, the financial system grew rapidly relative to the nonfinancial sector, rising from about 10 percent of value added and a 10 percent share of corporate profits to 20 percent of value added and 40 percent of corporate profits in the United States. To a large degree, this was because finance, instead of financing the capital development of the economy, was financing itself. At the same time, the capital development of the economy suffered perceptibly. If we apply a broad definition - to include technological advances, rising labor productivity, public and private infrastructure, innovations, and the advance of human knowledge - the rate of growth of capacity has slowed. [...]
Keywords: B5; B51; B52; G; G1; G2; H6; L5; N1; O1; O2; O3; O4; P1; 330; Banker as Ephor of Capitalism; Capital Development; Finance; Global Financial Crisis; Innovation; Minsky; Schumpeter